THE RESILIENCE OF THE INDONESIAN BANKING SYSTEM AND MACROECONOMIC FLUCTUATION: ISLAMIC VERSUS CONVENTIONAL BANKING - Muh. Rudi Nugroho; Ahmad Syakir Kurnia; Abdul Qoyum; Fitrotul Fardila (Bank Indonesia, 2020)
This study aims to analyze the challenges of the dual banking system during macroeconomic fluctuations. By using the default probability mapping method and macroeconomic stress testing, we can measure the stability of the financial system through credit calculation. In addition, by using the stress test method, we can find information about the characteristics of the financial system in crises and its financial-related assistance in the financial system. Considering if a financial system can detect it early, the government can take preventative measures to minimize the consequences. The results of the study show that Islamic banking has a higher default probability than conventional banking. So it can be concluded that the current stability of Islamic banking is not better than conventional banking. Our findings suggest that inflation is only a macroeconomic variable that has a high level of sensitivity to the default probability of banks. Moreover, Islamic and conventional banking have different responses to the sensitivity of inflationary interventions.